Inovasi Pengrajin Gerabah Dalam Meningkatkan Pendapatan Keluarga Di Desa Sugih Waras OKI - Nova Yanti Maleha; Waldi Nopriansyah; Bagus Setiawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research was conducted in Sugih Waras Village, Teluk Gelam District, Ogan Komering Ilir Regency, to find out the income of pottery craftsmen in Sugih Waras Village, Teluk Gelam District, Ogan Komering Ilir Regency. The research method used in this research is purposive sampling used to determine certain criteria that are considered as populations. From several interviews conducted by researchers, where the results of the interviews were almost all pottery craftsmen stated that sales and income for pottery craftsmen had decreased quite drastically, where people's purchasing power had fallen, thus reducing their income, so they didn't sell at all or closed their businesses. . The causes of the closing of the business are due to running out of capital and no capital, uncertain weather conditions, materials that are difficult to obtain, the emergence of designs with the latest innovations, some buyers prefer online shopping which uses their daily income to connect their survival in order to meet household needs for pottery craftsmen. Keywords: Innovation, Pottery, Income